Effects of a 6-week core stabilization training program on dynamic balance and trunk stabilization endurance of horse riders - Lam, N. H. K.; Lau, W. M.; Lau, T. L. (Sport Sciences for Health, 2021)
The purpose of this study was to examine the effectiveness of a 6-week core stabilization training program (CSTP) in improving dynamic balance and back-extensor endurance of horse riders; and develop a measurement tool in assessing the dynamic postural stabilization endurance for horse riders. Twelve male horse riders (age: 23.58 ± 1.93 years; height: 165.09 ± 4.60cm; weight: 56.53 ± 4.75 kg; experience in horse racing: 1.75 ± 0.34 years) completed 12 training sessions in 6 weeks. Subjects performed the CSTP with two progressions. CSTP started with the basic consciousness activation exercises, and then eliminated visual feedback in dynamic balance task on unstable surfaces and finished with switching the center of gravity. Moderate-to-large difference was demonstrated in the Y-Balance test scores for right leg (102.81 ± 8.32 vs 106.471 ± 4.35cm, d = 0.55, 95% CL 0.00 to 1.08) and left leg (102.04 ± 3.20 vs 106.29 ± 3.62 cm, d = 1.25, 95% CL 0.41 to 2.05) following 6 weeks CSTP. However, trivial to small differences was reported between left and right leg in pre (d = 0.12, 95% CL -0.49 to 0.73) and post 6-week CSTP (d = 0.04, 95% CL -0.69 to 0.78). Biering-Sørensen test (BST) shows largely greater performance after 6-week CSTP (98.3 ± 30.1 vs 131.8 ± 19.0s, d = 1.33, 95% CL 0.54-2.09). A novel measurement, Swiss ball four-point kneeling test was shown to be correlated with the change in BST (r = 0.633).